Impact of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Variant-Associated Receptor Binding Domain (RBD) Mutations on the Susceptibility to Serum Antibodies Elicited by Coronavirus Disease 2019 (COVID-19) Infection or Vaccination. (26th July 2021) - Chen, Lin-Lei; Lu, Lu; Choi, Charlotte Yee-Ki; Cai, Jian-Piao; Tsoi, Hoi-Wah; Chu, Allen Wing-Ho; Ip, Jonathan Daniel; Chan, Wan-Mui; Zhang, Ricky Ruiqi; Zhang, Xiaojuan; Tam, Anthony Raymond; Lau, Daphne Pui-Ling; et al.
Abstract: Background: Several severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) lineages with mutations at the spike protein receptor binding domain (RBD) have reduced susceptibility to antibody neutralization, and have been classified as variants of concern (VOCs) or variants of interest (VOIs). Here we systematically compared the neutralization susceptibility and RBD binding of different VOCs/VOIs, including B.1.617.1 (kappa variant) and P.3 (theta variant), which were first detected in India and the Philippines, respectively. Methods: The neutralization susceptibility of the VOCs/VOIs (B.1.351, B.1.617.1, and P.3) and a non-VOC/VOI without RBD mutations (B.1.36.27) to convalescent sera from coronavirus disease 2019 (COVID-19) patients or BNT162b2 vaccinees was determined using a live virus microneutralization (MN) assay. Serum immunoglobulin G (IgG) binding to wild-type and mutant RBDs were determined using an enzyme immunoassay. Results: The geometric mean neutralization titers (GMT) of B.1.351, P.3, and B.1.617.1 were significantly lower than that of B.1.36.27 for COVID-19 patients infected with non-VOCs/VOIs (3.4- to 5.7-fold lower) or individuals who have received 2 doses of BNT162b2 vaccine (4.4- to 7.3-fold lower). The GMT of B.1.351 or P.3 were lower than that of B.1.617.1. For the 4 patients infected with B.1.351 or B.1.617.1, the MN titer was highest for their respective lineage. RBD with E484K or E484Q mutation, either alone or in combination with other mutations, showed greatest reduction in serum IgG binding. Conclusions: P.3 and B.1.617.1 escape serum neutralization induced by natural infection or vaccine. Infection with 1 variant does not confer cross-protection for heterologous lineages. Immunogenicity testing for second generation COVID-19 vaccines should include multiple variant and "nonvariant" strains. Abstract : Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) theta (P.3) and kappa (B.1.617.1) variants can escape convalescent serum and vaccine-induced serum neutralizing response. The spike E484K mutation has the greatest impact on receptor binding domain (RBD) binding.